Brahma sutras : chatussutri - Vimalānanda Bhārati, Swami, 1878-1950 (s.n., 1978)
Interpretive study on the first four aphorisms of Bādarāyaṇa's Brahmasūtra, basic work on the Vedantic fundamentals, from the Advaita viewpoint.